KGB against former political prisoners and deportees - Burinskaitė, Kristina (Genocidas ir rezistencija, 2008)
The Soviet totalitarian regime sought to crush and destroy the real and potential enemies of the new regime through mass repression in Lithuania between 1940 and 1953. First, the Soviet repressive structures began to deport Lithuania’s political and social elite in order to avoid their possible resistance. The subsequent deportations were aimed at suppressing armed resistance and facilitating the implementation of collectivisation and sovietisation processes. However, the suffering and hardship of former exiles and prisoners in exile or in the camps did not end after they had served their sentences. They were met by an inhospitable and hostile Soviet Lithuanian government and repressive structures. The KGB paid special attention to certain social and societal groups and carried out agent-operative measures against them. They were seen as coming from a socially dangerous environment and what the KGB called a ‘negative environment’, which led to the use of various KGB methods and discrimination against them.